ANALISIS WACANA KRITIS MODEL TEUN A. VAN DIJK Dalam Iklan GoFood Versi Anak Baru di Youtube - Muhamad Aceng Nurhidayat (2021)
This study discusses the GoFood advertising the new chils's version, the advertisement displays a tutorial on how to order food through GoFood with vouchers specifically for new users. Unfortunately, the GoFood advertisement for the new children's version has a controversy and is not in accordance with existing ethics in the community so it is feared that it will have a negative effect on the community. So that researchers are interested in critical discourse analysis that exist in the the new chils's version of the GoFood advertisement in relation to the ideology, values, or interests of the advertiser. This study uses a discourse analysis research method with Teun A. Van Djik's model with the aim of the study being to analyze the dimensions of the text, find and analyze the meaning in the text through the dimensions of social cognition and analyze the discourse in the GoFood advertisement for the new children's version on the dimensions of social context. Van Djik sees a discourse not only through analysis of the text, but also sees how a text is produced so that we can find out why a text is the way it is. The results of this study show that in the text dimension there are discourses displayed by advertisers in order to introduce GoFood to new audiences. Then on the dimension of social cognition, advertisers display elements such as violence, and consumerism to attract audience users. Whereas in the dimension of social context there are discourses and elements that are not in accordance with the values that exist in society.